Mentoring strategy to improve the effectiveness of succession planning in PT Multimas Nabati Asahan - Serang - Sinaga, Sabam Frando; Ma’arif, M. Syamsul; Triyonggo, Yunus (International Journal Labs, 2025)
This study focuses on analyzing the influence of mentoring conducted by PT Multimas Nabati Asahan Serang on the effectiveness of succession planning, analyzing mentoring that has a dominant influence on succession effectiveness planning, and developing mentoring strategies to increase the effectiveness. The study involved a total of 22 departments within the organization and will span three months, from September 2024 to November 2024. The results of the Analytical Hierarchy Process (AHP) analysis showed that the employee competency factor is the most influential factor in succession planning. The data from the assessment of the weight and priority of alternative elements of strategies to the objectives showed the highest influence was collaborative learning with a weight value of 0.281 and then the second to fifth were alternative strategies for enrichment and expansion of work, project assignment, work rotation, and formal training.